FIGURATIVE LANGUAGE ANALYSIS ON THE UGLY LOVE NOVEL BY COLLEEN HOOVER - Tiarawati, Arini Egi; Ningsih, Tri Wahyu Retno (Universitas Gunadarma, 2019)
The aim of this study is to analyze the types of figurative language which found in Ugly Love novel by Colleen Hoover. This study used figurative language theory by Leech to analyze the data which the researcher found in the novel. The method of this study is descriptive qualitative method. The total of the data are 87 data to be analyzed in the types of figurative language. The data will be identify and classify into 8 types of figurative language by Leech. The result of this study found 6 types of figurative language in this Ugly Love novel. That are 33 data of personifications (33 data) , 19 data of similes, 11 data of irony, 10 data of hyperbole, 9 data of metaphors, and 5 data of metonymy. The most of dominant type of figurative language in the Ugly Love novel by Colleen Hoover is personification.